The talk goes outside: argument, privacy and power in Mambila society. Towards a sociology of embedded praxis - Zeitlyn, D (EDINBURGH UNIV PRESS, 2003)
In this paper the sociological implications of loud argument are considered, by taking a case study from the Mambila in Cameroon. Meetings of rotating credit societies are non-traditional forums where power and status are in dispute. These meetings contrast with both domestic arguments and with disputes held in the Chief's court. Rotating credit society meetings usually include arguments but these are dismissed as being unimportant by local informants. They pose a challenge for anthropological analysis since they are such a regular but disregarded-and disparaged-occurrence. Raised voices increase the range of bystanders as witnesses, so to argue loudly is a very social act.